A digitally printed optoelectronic nose for the selective trace detection of nitroaromatic explosive vapours using fluorescence quenching. (24th April 2017) - Bolse, N; Eckstein, R; Schend, M; Habermehl, A; Eschenbaum, C; Hernandez-Sosa, G; Lemmer, U
Abstract: We report on a fluorescent optoelectronic nose for the trace detection of nitroaromatic explosive vapours. The sensor arrays, fabricated by aerosol-jet printing, consist of six different commercially available polymers as transducers. We assess the within-batch reproducibility of the printing process and we report that the sensor polymers show efficient fluorescence quenching capabilities with detection limits of a few parts-per-billion in air. We further demonstrate the nose's ability to discriminate between several nitroaromatics including nitrobenzene, 1, 3-dinitrobenzene and 2, 4-dinitrotoluene at three different concentrations using linear discriminant analysis. Our approach enables the realization of highly integrated optical sensor arrays in optoelectronic noses for the sensitive and selective detection of nitroaromatic explosive trace vapours using a potentially low-cost digital printing technique suitable for high-volume fabrication.